(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
Complexation and speciation of copper (II) in ppb level with 1,10-phenanthroline (L) in aqueous media have been investigated by differential pulse anodic stripping voltammetry using thin mercury film glassy carbon electrode (TMFGCE). The work was carried out at constant ionic strength of 0.01 mol dm-3 using NaNO3 at ambient temperature. The pH was kept constant at 9.12 ± 0.10 by the addition of borate buffer. Applying the concept of DeFord and Hume, the stability constants of different species of copper with 1,10-phenanthroline were calculated from the variation of peak potential and diffusion current of simple and complexed metal ions under the present experimental conditions. It was found that copper(II) form three complexes (1:1, 1:2 and 1: 3; metal : ligand) with 1,10-phenanthroline. The overall stability constant of copper complexes, MLn can be defined as βMLn= [MLn ]/[M2+][L]n in which M2+ = Cu2+ and L = 1,10-phenanthroline; n is an integer. The values of the stability constant of different copper complexes with 1,10-phenanthroline were found to be 109.33, 1015.10 and 1020.48 for CuL, CuL2 and CuL3, respectively (the overall charges were omitted for simplicity). The high values of overall stability constant indicate that the complexes are highly stable. Using the values of stability constant of copper complexes and hydrolysis constant of copper, the percentage of all possible copper species under present experimental conditions were calculated. Keywords: Electrochemical; Speciation; Complexation; Copper 1,10-phenanthroline. DOI: http://dx.doi.org/10.3329/bjsir.v46i2.8188 Bangladesh J. Sci. Ind. Res. 46(2), 219-224, 2011